Kuasa Uang dalam Pemilihan Kepala Daerah: Oligarki, Premanisme dan kekuatan Lokal - Muhtar; Atikah Khairunnisa; Joana Tuhumury (Journal of Literature Review, 2025)
This study explores the relationship between money power, oligarchy, thuggery, and local power in regional head elections, which collectively form a transactional patronage network. Drawing on Oligarchic Power Theory (Winters, 2011), this study shows that oligarchs use wealth to dominate politics, both in campaign funding and post-election policy influence. Coercive Clientelism (Wilson, 2015) explains that thuggery functions as a tool for mass mobilization, intimidation of political opponents, and securing votes in certain areas, strengthening the dominance of local elites. Furthermore, Berenschot (2018) identifies village heads and local figures as mediators in the distribution of money politics, which plays a crucial role in strengthening patron-client relationships at the grassroots level. This phenomenon supports clientelism theory, where money power is the primary link between oligarchs, candidates, and local communities. This study also reflects the plutocracy trap (Winters, 2011), where wealth is used to control public policy and reduce political accountability. The power of money enables patronage networks to operate systematically to produce policies biased toward elite interests, while simultaneously weakening the quality of local democracy. The theoretical contribution of this research is to broaden understanding of the interaction between economic power, social control, and local networks in transactional politics. These findings highlight the need for political reform to reduce the influence of oligarchs, strengthen transparency in political funding, and increase accountability in local democratic processes. This research provides a foundation for further study on strategies to improve democracy in Indonesia, particularly in the context of regional head elections as a means of local democracy.